Conformational characterization of full-length X-chromosome-linked inhibitor of apoptosis protein (XIAP) through an integrated approach. (2019) - Polykretis, Panagis; Luchinat, Enrico; Bonucci, Alessio; Giachetti, Andrea; Graewert, Melissa A.; Svergun, Dmitri I.; Banci, Lucia
No abstract available